Performance measures for upper gastrointestinal endoscopy: a European Society of Gastrointestinal Endoscopy (ESGE) Quality Improvement Initiative – Update 2025 - Areia, Miguel; Esposito, Gianluca; Leclercq, Philippe; Romańczyk, Marcin; Zessner-Spitzenberg, Jasmin; Delgado Guillena, Pedro G.; Monged, Ashraf; Honrubia López, Raul; Uchima, Hugo; Ruiz Ballesteros, Eduardo J.; Panarese, Alba; Reis de Oliveira, Lix Alfredo; Afify, Shimaa; Bisschops, Raf; Ferlitsch, Monika; External Voting Panel; Arvanitakis, Marianna; Barthet, Marc; Bhandari, Pradeep; Boskoski, Ivo; Bretthauer, Michael; Fuccio, Lorenzo; Gralnek, Ian M.; Hassan, Cesare; Hritz, Istvan; Lorenzo-Zúñiga, Vincente; Papanikolaou, Ioannis S.; Rodríguez de Santiago, Enrique; Siersema, Peter D.; Tham, Tony C.; Triantafyllou, Konstantinos; Voiosu, Andrei (Endoscopy, 2025)
Quality markers and patient experience should be implemented to ensure standardization of practice across upper gastrointestinal (UGI) endoscopy procedures. The set benchmarks ensure high quality procedures are delivered and linked to measurable outcomes. In 2016, the European Society of Gastrointestinal Endoscopy (ESGE), via its Quality Improvement Committee’s UGI Working Group, set a first list of performance measures, including major (key) and minor performance indicators. This paper provides an update on those performance measures, considering the latest literature.Patients referred for a UGI endoscopy should have an appropriate indication and be fasting for ≥ 2 hours for liquids and ≥ 6 hours for solids.For a diagnostic UGI endoscopy, patients should have an allocated time slot of ≥ 20 minutes; adequate reporting should include a mucosal visibility score according to one of the available standardized and validated scales; adequate photodocumentation should include relevant normal anatomical landmarks and all abnormal findings; adequate inspection should include the esophagus, stomach, and duodenum, and should last ≥ 7 minutes from intubation to extubation; adequate terminology should include the description of any abnormal finding according to the available standardized and validated classifications.For patients with nondysplastic Barrett’s esophagus (BE) undergoing surveillance UGI endoscopy, an adequate inspection should take ≥ 1 minute/cm of circumferential extent of Barrett’s epithelium and include the use of chromoendoscopy (acetic acid and/or virtual); biopsies should be taken according to the Seattle protocol.Adequate inspection for a diagnostic UGI endoscopy in patients with a history of ear, nose, and throat, or lung tumors treated with curative intent should include the use of virtual chromoendoscopy.Adequate diagnostic UGI endoscopy for patients evaluated for their risk of gastric cancer should include biopsies taken according to the ESGE management of precancerous conditions and lesions in the stomach (MAPS) guideline.Adequate safety after a therapeutic UGI endoscopy should be assessed by monitoring the incidence of complications.Patients undergoing a diagnostic UGI endoscopy should have their experience measured using a validated scale, to promote a patient-centered and quality-driven environment.Patients with nondysplastic BE or gastric precancerous conditions in an endoscopic surveillance program should be monitored for guideline interval adherence.